2021
DOI: 10.4103/aian.aian_1316_20
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal Deep Brain Stimulation for KMT2B Related Dystonia in An Indian Patient

Abstract: Outcomes of pallidal stimulation in KMT2B dystonia have been infrequently reported prospectively. We report the six-month outcomes of bilateral GPi DBS in an Asian Indian patient with early-onset generalized dystonia associated with a novel heterozygous variant in the KMT2B gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…1). [15][16][17][18][21][22][23][24][25][26] We found a total of 42 subjects with DYT-KMT2B who underwent GPi-DBS and had pre-and postoperative outcome data available. Number of patients reported in individual studies ranged from 1 to 17.…”
Section: Resultsmentioning
confidence: 99%
“…1). [15][16][17][18][21][22][23][24][25][26] We found a total of 42 subjects with DYT-KMT2B who underwent GPi-DBS and had pre-and postoperative outcome data available. Number of patients reported in individual studies ranged from 1 to 17.…”
Section: Resultsmentioning
confidence: 99%
“…Several adult and pediatric patients underwent GPi-DBS due to DYT-THAP1 and DYT-KMT2B. Although the number of pediatric patients was lower, the results prove that bilateral GPi-DBS is a valuable therapeutic option for DYT-THAP1 (8)(9)(10)(11)(12)(13)(14)(15)(16) and DYT-KMT2B, particularly for movement disorders and regaining mobility, but less so for speech issues (5,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) (Supplementary Tables 1, 2). So far, the aforementioned patients presented with severe dystonic postures, majorly impacting their quality of life, as well as those of their families and caregivers.…”
Section: Discussionmentioning
confidence: 94%
“…Further clinical characteristics, such as cognitive disability, psychiatric comorbidities, and dysmorphic features, have been reported in several patients (27-29). Bilateral GPi-DBS has been reported as an efficient therapeutic option, especially for improving movement disorder and regaining independent mobility (5,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). GPi-DBS is sometimes associated with "dramatic" amelioration in gait but more commonly associated with truncal dystonia and scoliosis; it is rarely associated with speech dysfunction in severely affected patients with KMT2B gene mutations prior to DBS (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBS is the preferred treatment modality for patients with isolated dystonia without CNS degeneration or insult is because it is reversible. [22][23][24][25][26][27] However, the advantages of DBS in patients with acquired/heredodegenerative dystonia are not definite. 26,28,29 A recent multicenter, single-arm, randomized, double-blind crossover trial on the effect of DBS in pediatric dystonia patients with dyskinetic cerebral palsy concluded that the evidence is insufficient to recommend DBS as routine treatment for these patients.…”
Section: Role Of Pallidotomy In the Era Of Dbsmentioning
confidence: 99%